TINGKAT KETERBACAAN READING MATERIALS DALAM MATA KULIAH TELAAH TEKS BAHASA INGGRIS STAIN PAMEKASAN - Mulyadi — (Research Institute and Community Engagement of IAIN MADURA, 2011)
This Article is summarized from a research report about reading level of textbook of English text study subject in STAIN Pamekasan. Reading level is measure about according to not it a reading to certain reader seen from level facet of difficulty / amenity its discourse. This research target is to describing the reading level of reading materials of English text study subject in STAIN Pamekasan. English subject is studied in two levels, namely, elementary level calls the English subject and also advanced level is English Text Study. This two subjects have the character to be obliged to go through for all college students in five studies program (prodi) — Islamic Religion education, Arab language education, and English education in Tarbiyah Department. Two other studies program are Islam Civil Law and Moslem law Banking in Moslem law Department. By using the analytical descriptive method expected can give the reading level of textbook pursuanting to understanding of college students can be explained. Its source data is from all textbooks taught at English text study subject in STAIN Pamekasan. The research result indicates that most existing discourse in textbooks taught is standard classification. for that is suggested to curator lecturer of English text study subject to be more selective in discourse election its textbooks. Boosting up difficulty level undoubted to be done by paying attention of lecturing technique “reading” for the students facility comprehend textbooks